2017
DOI: 10.1111/ldrp.12143
|View full text |Cite
|
Sign up to set email alerts
|

College Students With ADHD and LD: Effects of Support Services on Academic Performance

Abstract: Two relatively common disabilities reported by college students are attentiondeficit/hyperactivity disorder (ADHD) and learning disabilities (LD). Many questions remain regarding how best to support these students and whether services such as advising, coaching, and tutoring lead to significant academic gains. The current study examined the effect of support services on the GPA of students with LD and/or ADHD at a campus that specifically serves this population by tracking students' support service usage and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 40 publications
3
41
0
2
Order By: Relevance
“…Consistent with the current study, research conducted by DuPaul, Dahlstrom-Hakki et al (2017) also indicated that students with LD benefit from the use of some universally available supports. Moreover, the current findings extend those of DuPaul et al by establishing that students with LD benefit from universally available services in terms of not only GPA but also college completion.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with the current study, research conducted by DuPaul, Dahlstrom-Hakki et al (2017) also indicated that students with LD benefit from the use of some universally available supports. Moreover, the current findings extend those of DuPaul et al by establishing that students with LD benefit from universally available services in terms of not only GPA but also college completion.…”
Section: Discussionsupporting
confidence: 84%
“…However, equal emphasis is needed on helping students to identify and access universally available supports on campus. Prior research (e.g., DuPaul, Dahlstrom-Hakki et al, 2017;Newman et al, under review) and the current study have demonstrated that such academic supports increase the likelihood of student persistence and/or completion. Clearly, transitioning students need not only to be aware of but be prepared to access such services once on campus.…”
Section: Implications For Secondary Transitionsupporting
confidence: 53%
“…As a defining deficit for ADHD, poor sustained attention could compromise the value of time spent studying, regardless of study planning or environmental characteristics. A number of interventions for addressing poor sustained attention exist, including training in time management, organization, and self‐awareness (Kaminski et al, ), academic coaching (DuPaul et al, ; Parker, Hoffman, Sawilowsky, & Rolands, ), and use of ADHD medication (Greenhill et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Students diagnosed with dyslexia were found to have a disadvantage under time pressure and a pervasive problem with mathematical calculations (Callens, Tops, & Brysbaert, 2012) and semantic fluency (Hall, McGregor, & Oleson, 2017). Evidence is accumulating that participation in a learning support program helps students with LD to cope with these challenges and improve their GPA (DuPaul et al, 2017) as well as enhance their likelihood of graduating (Troiano, Liefeld, & Trachtenberg, 2010).…”
Section: Academic Support For Students With Ldmentioning
confidence: 99%
“…The above reviewed studies provide a description of the various support services available for students with LD; however, there is a need to examine to what degree different support programs contribute to the college achievements of students with LD. One study that investigated this question in the United States was that of DuPaul et al (2017), who compared, in a sample of students with LD or attention-deficit/hyperactivity disorder (ADHD; n = 1,592), the effect of the number of hours received in three support services (advising, coaching, and tutoring) on students’ semester GPAs over a 5-year period. Their findings revealed that students with LD who participated either in tutoring or coaching showed gains in their semester GPA.…”
Section: Academic Support For Students With Ldmentioning
confidence: 99%